The global impact and legacy of truth commissions / edited by Jeremy Sarkin. - Sarkin-Hughes, Jeremy (Series on transitional justice, 2019)
The Global Impact and Legacy of Truth Commissions emerges at a time when there is a confluence of two trends. The first is a growing critique of truth commissions as being unresponsive to the socio-economic needs of transitional societies as part of growing criticism of transitional justice as a whole. The second is the increasing use, salience, professionalism and ambition of truth commissions. Thus, the book is published at a time when truth commissions are being both doubted and reified like never before. In this context, the book's purpose is to understand the impact and legacy of these institutions over the past fifty years. Bringing together many prominent voices on the topic, this book investigates what kind of impact and legacy (possibly 100) truth commissions have had on the societies in which they have taken place, and for future truth commissions the world over.